Produção de biomassa e exportação de nutrientes de Eucalyptus grandis e E. urophylla - Habitzreiter, Tiago Luis (2016)
Scientific research in forest production technology area search techniques that increase production per unit area, with high economic viability and reducing environmental impacts. When dealing with forest plantations, studies are needed in the production of biomass and its nutrient content, and these are data parameters for planning the environmental implications of different intensities of forest harvesting. Given the above, this study aimed to elucidate the production and export of biomass and nutrients for two species of the genus Eucalyptus (E. grandis and E. urophylla) grown in the southwestern region of Parana. For this, it was evaluated: the stock of biomass and nutrients in eucalyptus (wood, bark, branches and leaves) at 60 months of age; the export rate of nutrients; the calorific value and economic viability. The biomass and the largest eucalyptus nutrient stocks are predominantly allocated to the stem (wood + bark). The components of biomass showed different chemical compositions, generally being higher in the leaves and bark and lower in wood and branches components. As for the calorific value, the leaves had its calorific value statistically superior than the other fractions, followed by branches, wood and bark. The organic carbon content (C.O.) is directly connected to the calorific value, and the calorific value increases as its content increase. The wood had the highest nutrient use efficiency values, something highly desirable and of great interest to forestry. The leaves showed smaller nutrient utilization efficiency values, with the exception of Ca and Mg that were smaller in the bark, indicating the importance of maintaining these components in the soil after harvest. The wood fraction presents the biomass lower cost when considering the replacement of nutrients exported by its biomass. On the other hand, the leaf fraction showed NPK higher cost of replacement.